Advances in Stem Cell Research- A Ray of Hope in Better Diagnosis and Prognosis in Neurodegenerative Diseases - Singh, Shripriya; Srivastava, Akriti; Srivastava, Pranay; Dhuriya, Yogesh K.; Pandey, Ankita; Kumar, Dipak; Rajpurohit, Chetan S. (Frontiers in Molecular Biosciences, 2016)
Neurodegeneration and neurodegenerative disorders have been a global health issue affecting the aging population worldwide. Recent advances in stem cell biology have changed the current face of neurodegenerative disease modeling, diagnosis and transplantation therapeutics. Stem cells also serve the purpose of a simple in-vitro tool for screening therapeutic drugs and chemicals. We present the application of stem cells and induced pleuripotent stem cells (iPSCs) in the field of neurodegeneration and address the issues of diagnosis, modeling and therapeutic transplantation strategies for the most prevalent neurodegenerative disorders. We have discussed the progress made in the last decade and have largely focused on the various applications of stem cells in the neurodegenerative research arena.